AUTOIMMUNE POLYGLANDULAR SYNDROME (APS) TYPE 2 WITH CENTRAL DIABETES INSIPIDUS - Mahfuza, Ummul; Preda, Martina; Preda, Veronica (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGOUND APS involves functional abnormalities in several endocrine and non-endocrine glands. Deficits may manifest over time. Screening for other manifestations is important. The major components of the syndrome are adrenal insufficiency, thyroid autoimmunity and type 1 diabetes. It is very rarely described with central diabetes insipidus (DI). We present a very uncommon presentation of APS-2 with the onset of Addison’s at age 7, developing other polyglandular associations over time and central DI in adulthood. CASE A 31-year-old woman with a history of Addison’s disease diagnosed and treated with dexamethasone at age 7 presented with acute polyuria and polydipsia. She had negative water deprivation test according to the North Bristol protocol. Due to persistent symptoms, she was empirically commenced on desmopressin (Minirin) with good response. Testing finally diagnosed central DI: magnetic resonance imaging (MRI) demonstrated absence of the posterior pituitary bright spot and a 3 mm stalk thickening thought to be pathognomonic and possibly related to arginine vasopressin antibody status. Antibodies to thyroglobulin, thyroid receptor, ZnT8, GAD and IA2 were negative. TSH and HbA1c were normal. CONCLUSION APS-2 as an evolving polyglandular disease may be associated with other endocrine deficiencies, including central DI. Loss of pituitary bright spot and stalk thickening on MRI supports the diagnosis of central DI and should be considered in the work up of patients.